Phylogenetic Analysis of Culex tritaeniorhynchus and Culex vishnui Vector of Japanese Encephalitis Virus - Raden Wisnu Nurcahyo; R.C. Hidayat Soesilohadi; Suwarno Hadisusanto; Budi Mulyaningsih; Raden Roro Upiek Ngesti Wibawaning Astuti (Global Medical & Health Communication (GMHC), 2019)
Culex tritaeniorhynchus and Culex vishnui are medically essential mosquitoes that transmit the Japanese encephalitis (JE) virus. There is less information about the recording data and research due to genetic character differences among them. The objective of this study was to examine the genetic variation of Cx. tritaeniorhynchus and Cx. vishnui in 3 sites of Central Java using polymerase chain reaction randomly amplified polymorphic DNA (PCR-RAPD). The study was done in January to November 2017 in Pekalongan city, Pekalongan regency, and Semarang regency. Adult female mosquitoes collected by human bite method. DNA of ten Cx. tritaeniorhynchus samples and fifteen samples of Cx. vishnui purified using DNA extraction kit. Furthermore, PCR amplification was conducted with 5 RAPD primers (OPA 11, 12, 15, 16, and 20) and would run into 2% gel electrophoresis for 45 minutes. Cluster analysis was using MVSPTM software (version 3.1). The results showed 213 genetic characters of Cx. vishnui, while 142 characters shown by Cx. tritaeniorhynchus. The dendrograms showed three distinct groups of Cx. vishnui from 2 sites of Pekalongan and one site of Semarang, while Cx. tritaeniorhynchus showed two distinct groups, which were 1 group from Pekalongan and 1 group from Semarang. Low genetic similarity (<10%) shown Cx. vishnui from Pekalongan city and Pekalongan district, and there was no genetic similarity in Cx. tritaeniorhynchus from Pekalongan and Semarang. It concluded that the polymorphism of Cx. tritaeniorhynchus and Cx. vishnui reached 100%. ANALISIS FILOGENETIK CULEX TRITAENIORHYNCHUS DAN CULEX VISHNUI VEKTOR VIRUS JAPANESE ENCEPHALITISNyamuk Culex tritaeniorhynchus dan Culex vishnui memiliki peran penting di bidang medis terutama dalam penularan virus Japanese  encephalitis (JE). Sampai saat ini data dan riset tentang karakter genetik vektor JE masih sangat terbatas. Penelitian ini bertujuan menjelaskan variasi genetik Cx. tritaeniorhynchus dan Cx. vishnui di 3 lokasi di Jawa Tengah berdasar polymerase chain reaction randomly amplified polymorphic DNA (PCR-RAPD). Studi ini dilakukan dari bulan Januari sampai November 2017 di Kota Pekalongan, Kabupaten Pekalongan, dan Kabupaten Semarang. Metode human bite digunakan untuk koleksi nyamuk. Ekstraksi DNA nyamuk dilakukan pada 10 ekor Cx. tritaeniorhynchus dan 15 ekor Cx. vishnui menggunakan kit ekstraksi DNA. Selanjutnya, diamplifikasi dengan 5 macam primer RAPD (OPA 11, 12, 15, 16, dan 20), serta dielektroforesis pada 2% agar selama 45 menit. Analisis klaster dilakukan menggunakan program MVSPTM (versi 3.1). Ditemukan 213 dan 142 karakter genetik masing-masing pada Cx. vishnui dan Cx. tritaeniorhynchus. Analisis dendogram menunjukkan 3 grup yang berbeda untuk Cx. vishnui, sedangkan untuk Cx. tritaeniorhynchus terdapat 2 grup yang berbeda, yaitu 1 grup dari Pekalongan dan 1 grup dari Semarang. Similaritas genetik yang rendah (<10%) ditunjukkan Cx. vishnui dari Kota Pekalongan dan Kabupaten Pekalongan, bahkan tidak ada persamaan genetik pada Cx. tritaeniorhynchus dari Pekalongan dengan Semarang. Disimpulkan bahwa polimorfisme Cx. tritaeniorhynchus dan Cx. vishnui mencapai 100%.